Quantifying the wind energy potential differences using different WRF initial conditions on Mediterranean coast of Chile. (1st December 2019) - González-Alonso de Linaje, N.; Mattar, C.; Borvarán, D.
Abstract: In this work, a comprehensive analysis of WRF initial conditions was performed to estimate the offshore wind power on the coasts of the IV region of Coquimbo, Chile. Three configurations of atmospheric physical models accounting for the planetary boundary layer and surface layer were put under consideration. In addition, sensitivity was estimated by using four physical-numerical simulations: spectral nudging, surface model, 10-days restart and definition of vertical levels. Simulations were carried out for January and July 2013. The results show that the initial condition composed of physical schemes MYNN3 – MYNN – Noah (C3) has the lowest RMSE and highest r 2 with 1.748 m s −1 and 0.755 for January, and 2.512 m s −1 RMSE and 0.472 r 2 for July. In the sensitivity analysis, the configuration of vertical levels (S3) has the lowest RMSE with 1.812 m s-1 and the highest r2 with 0.732. High seasonal variability between January and July 2013 and WRF initial conditions have an impact on the estimation of the wind power and technical feasibility indicators in the study area, with differences between simulated and LV data in the range of 0.01%–36.3%. Highlights: WRF initial conditions were tested in order to estimate the offshore wind fields. High seasonal variability between January and July 2013 were evidenced. WRF Initial conditions have to be assessed before any simulation in Chile. Government energy strategies can be considered using off-shore wind power results.